2021
DOI: 10.2196/27883
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Exposure of Residents Living Close to Agricultural Fields in the Netherlands: Protocol for an Observational Study

Abstract: Background Application of pesticides in the vicinity of homes has caused concern regarding possible health effects in residents living nearby. However, the high spatiotemporal variation of pesticide levels and lack of knowledge regarding the contribution of exposure routes greatly complicates exposure assessment approaches. Objective The objective of this paper was to describe the study protocol of a large exposure survey in the Netherlands assessing pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…The eligibility criteria for the selection of studies were based on analyses of existing extensive biomonitoring studies such as Figueiredo et al [21], Vermeulen et al [16] and Galea et al [10,19,22,23]. In short, studies deficient in one or more of the following criteria were excluded:…”
Section: Selection Of Eligible Studiesmentioning
confidence: 99%
“…The eligibility criteria for the selection of studies were based on analyses of existing extensive biomonitoring studies such as Figueiredo et al [21], Vermeulen et al [16] and Galea et al [10,19,22,23]. In short, studies deficient in one or more of the following criteria were excluded:…”
Section: Selection Of Eligible Studiesmentioning
confidence: 99%
“…For human exposure modelling, the OBO exposure module will be used. This module consists of an a priori defined set of equations [ 29 ] and includes both human specific input and some more general and specific inputs from CSS. A brief summary of the model input is presented below:…”
Section: Ppp Modellingmentioning
confidence: 99%
“…Furthermore, previous studies show that people are rarely exposed to a single pesticide but, rather, to "cocktails" (mixtures) of different pesticides. 28 In fact, a previous study found virtually no associations between individual pesticides and the performance on motor or cognitive tests, but did find an association of overall pesticide exposure with these outcomes. 29 Mixtures of pesticides may well be associated with additive toxicity and possibly even have a synergistic effect.…”
mentioning
confidence: 90%
“…Studies in the general population have given mixed results, with some studies reporting that individuals who live in agricultural regions have an increased risk of PD, 26,27 suggesting that exposure to pesticides may contribute to the etiology of PD not only in farmers but also in a considerably larger proportion of PD cases. Furthermore, previous studies show that people are rarely exposed to a single pesticide but, rather, to “cocktails” (mixtures) of different pesticides 28 . In fact, a previous study found virtually no associations between individual pesticides and the performance on motor or cognitive tests, but did find an association of overall pesticide exposure with these outcomes 29 .…”
mentioning
confidence: 98%